Differential Proteomics of Cardiovascular Risk and Coronary Artery Disease in Humans - Ferrannini, Ele; Manca, Maria Laura; Ferrannini, Giulia; Andreotti, Felicita; Andreini, Daniele; Latini, Roberto; Magnoni, Marco; Williams, Stephen A.; Maseri, Attilio; Maggioni, Aldo P. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Proteomics of atypical phenotypes may help unravel cardiovascular disease mechanisms. Aim We aimed to prospectively screen the proteome of four types of individuals: with or without coronary artery disease (CAD), each with or without multiple risk factors. Associations with individual risk factors and circulating biomarkers were also tested to provide a functional context to the protein hits. Materials and Methods The CAPIRE study (ClinicalTrials.gov Identifier: NCT02157662) is a cross-sectional study aimed at identifying possible new mechanisms promoting or protecting against atherothrombosis. Quantification (by aptamer technology), ranking (using partial least squares), and correlations (by multivariate regression) of 5000 plasma proteins were performed in consecutive individuals aged 45-75 years, without previous cardiovascular disease, undergoing computed tomography angiography for suspected CAD, showing either >5/16 atherosclerotic segments (CAD+) or completely clean arteries (CAD–) and either ≤1 risk factor (RF+) or ≥3 risk factors (RF–) (based on history, blood pressure, glycemia, lipids, and smoking). Results Of 544 individuals, 39% were atypical (93 CAD+/RF–; 120 CAD–/RF+) and 61% typical (102 CAD+/RF+; 229 CAD–/RF–). In the comparison with CAD+/RF– adjusted for sex and age, CAD–/RF+ was associated with increased atrial myosin regulatory light chain 2 (MYO) and C-C motif chemokine-22 (C-C-22), and reduced protein shisa-3 homolog (PS-3) and platelet-activating factor acetylhydrolase (PAF-AH). Extending the analysis to the entire cohort, an additional 8 proteins were independently associated with CAD or RF; by logistic regression, the 12-protein panel alone discriminated the four groups with AUCROC’s of 0.72-0.81 (overall p=1.0e-38). Among them, insulin-like growth factor binding protein-3 is positively associated with RF, lower BMI, and HDL-cholesterol, renin with CAD higher glycated hemoglobin HbA1c, and smoking. Conclusions In a CCTA-based cohort, four proteins, involved in opposing vascular processes (healing vs adverse remodelling), are specifically associated with low CAD burden in high CV-risk individuals (high MYO and C-C-22) and high CAD burden in low-risk subjects (high PS-3 and PAF-AH), in interaction with BMI, smoking, diabetes, HDL-cholesterol, and HbA1c. These findings could contribute to a deeper understanding of the atherosclerotic process beyond traditional risk profile assessment and potentially constitute new treatment targets.